The transparency of the South African Reserve Bank - Anna Oksiutycz (Communicare)
The South African Reserve Bank (SARB) is a central bank. It is the public institution responsible for managing the South African monetary policy. Any decisions taken by the bank and how these decisions are communicated affect all the participants in the economic activity of the country. This study undertook a thematic analysis of the media releases, monetary policy statements and SARB Governors’ speeches delivered between 2008 and 2009. It revealed that the SARB, through having achieved a relatively high level of economic and policy transparency, achieved lower procedural and political transparency. The results also indicate that, despite there being an increased demand for the accountability of organisations to a broad spectrum of stakeholders, the SARB directs most of its communications to only a relatively limited group of stakeholders.